The architecture of mammalian ribosomal protein promoters - Perry Robert P (BMC Evolutionary Biology, 2005)
Abstract Background Mammalian ribosomes contain 79 different proteins encoded by widely scattered single copy genes. Coordinate expression of these genes at transcriptional and post-transcriptional levels is required to ensure a roughly equimolar accumulation of ribosomal proteins. To date, detailed studies of only a very few ribosomal protein (rp) promoters have been made. To elucidate the general features of rp promoter architecture, I made a detailed sequence comparison of the promoter regions of the entire set of orthologous human and mouse rp genes. Results A striking evolutionarily conserved feature of most rp genes is the separation by an intron of the sequences involved in transcriptional and translational regulation from the sequences with protein encoding function. Another conserved feature is the polypyrimidine initiator, which conforms to the consensus (Y)2C+1TY(T)2(Y)3. At least 60 % of the rp promoters contain a largely conserved TATA box or A/T-rich motif, which should theoretically have TBP-binding capability. A remarkably high proportion of the promoters contain conserved binding sites for transcription factors that were previously implicated in rp gene expression, namely upstream GABP and Sp1 sites and downstream YY1 sites. Over 80 % of human and mouse rp genes contain a transposable element residue within 900 bp of 5' flanking sequence; very little sequence identity between human and mouse orthologues was evident more than 200 bp upstream of the transcriptional start point. Conclusions This analysis has provided some valuable insights into the general architecture of mammalian rp promoters and has identified parameters that might coordinately regulate the transcriptional activity of certain subsets of rp genes.